Accounting in budgetary organizations: problems and ways of its improvement. (Journal of Economic Research & Business Administration, 2016)
Worldwide changing demands for action and accountability of government. These requirements form the basis of increasing responsibility for the effective financial management, with the aim of making the transition from cost management to the management of results and the medium-term Performance-based budgeting. Currently, the economy of the Republic of Kazakhstan is a highly developed information system, rebuilt and operated in accordance with international standards, a uniform system of accounting, which includes various aspects of it. High-quality reporting is necessary for the development of the capital market, often determines the economic development for decades to come.
Keywords: accounting; reporting; budgeting; public financial management.